2017
DOI: 10.22146/ijc.24252
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Conditions of Carboxymethyl Chitosan Synthesis on Drug Delivery Application and Its Release of Kinetics Study

Abstract: In this paper, carboxymethyl chitosan (CMC) was synthesized and studied as a carrier to encapsulate vitamin (as drug model) and controlled release. Chitosan (CS) is a polycationic derivated from chitin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…This causes the hydrated water molecules that around the chain of CMCH are more than that surrounding the chitosan chains, resulting in higher water solubility [ 30 ]. This results also are consistent with the report of Siahaan et al [ 31 ] who found that the temperature and NaOH concentration affected to CMCH synthesis. The interactions between NaOH and monochloroacetic acid resulted in reduced CMCH forming and lower solubility.…”
Section: Resultssupporting
confidence: 93%
“…This causes the hydrated water molecules that around the chain of CMCH are more than that surrounding the chitosan chains, resulting in higher water solubility [ 30 ]. This results also are consistent with the report of Siahaan et al [ 31 ] who found that the temperature and NaOH concentration affected to CMCH synthesis. The interactions between NaOH and monochloroacetic acid resulted in reduced CMCH forming and lower solubility.…”
Section: Resultssupporting
confidence: 93%
“…GO can interact with CMCS and PVA by hydrogen bonding. Thus, GO could act as crosslinker and increase rigidity of both first (CMCS) and second hydrogel (PVA) . The enhanced rigidity resulted in improved tensile strength and modulus.…”
Section: Resultsmentioning
confidence: 99%
“…We selected CMC instead of a virgin chitosan, which is one of the most studied polysaccharides nowadays with a wide number of applications in pharmacology and medicine, because a Folin-Ciocalteu's test with pristine chitosan gives a positive detection result, making it unfavorable for the presence study. Furthermore, it has been reported that CMC efficiency in drug carrier formulation is higher than with the unmodified chitosan 34 . Besides, by introducing the carboxymethyl hydrophilic groups to the chitosan structure, the CMC polymer becomes water soluble.…”
Section: Resultsmentioning
confidence: 99%